Factors associated with exclusive breastfeeding success among breastfeeding mothers in Ogan Komering Ulu Regency, Indonesia: A cross-sectional study - Ranida Arsi; Ulva Rachmawati; Fitri Afdhal (School of Health Sciences Al-Ma'arif, 2026)
Background: Exclusive breastfeeding is an essential intervention for improving infant health, growth, and development. Despite its well-established benefits, the coverage of exclusive breastfeeding in several regions of Indonesia remains below target, including in the working area of Puskesmas Peninjauan, Ogan Komering Ulu Regency. The success of exclusive breastfeeding is influenced by multiple maternal and environmental factors, including maternal knowledge, family support, parity, and pregnancy interval. Objective: This study aimed to analyze the factors associated with the success of exclusive breastfeeding among breastfeeding mothers in the working area of Puskesmas Peninjauan, Ogan Komering Ulu Regency. Methods: This study employed an analytical quantitative design with a cross-sectional approach. The study was conducted from June to July 2025 and involved all mothers with infants aged 7–12 months in the working area of Puskesmas Peninjauan, with a total of 61 respondents selected using total sampling. Data were collected using a checklist form and structured questionnaires covering maternal knowledge, family support, parity, pregnancy interval, and exclusive breastfeeding success. Data were analyzed using univariate and bivariate analyses with the Chi-square test at a 95% significance level (α = 0.05). Results: Most respondents were aged 21–30 years (52.5%), had completed senior high school (37.7%), and were homemakers (88.5%). A total of 91.8% of mothers successfully practiced exclusive breastfeeding. Bivariate analysis showed that family support was significantly associated with exclusive breastfeeding success (p = 0.002), whereas maternal knowledge (p = 0.353), parity (p = 0.215), and pregnancy interval (p = 0.052) were not significantly associated. Conclusion: Family support was the most influential factor associated with the success of exclusive breastfeeding. Strengthening the involvement of husbands and family members in breastfeeding education and lactation support should be integrated into maternal and child health services to improve exclusive breastfeeding outcomes.